The Role of MGMP in Developing Professional Competence of Indonesian Language Teachers - Aulan Malik Pajar; Vebby Andra; Hengki Satrisno (Yayasan Karinosseff Muda Indonesia, 2023)
The problems raised in this study are How is the role of Subject Teacher Deliberation (MGMP) in developing the professional competence of Indonesian language teachers at SMPN 21 Bengkulu City and How is the form of factors inhibiting the role of Subject Teacher Deliberation (MGMP) in developing the professional competence of Indonesian language teachers at SMPN 21 Bengkulu City. The purpose of this study was to determine the role of Subject Teacher Conference (MGMP) in developing the professional competence of Indonesian language teachers at SMPN 21 Bengkulu City and the form of inhibiting factors of Subject Teacher Conference (MGMP) in developing the professional competence of Indonesian language teachers at SMPN 21 Bengkulu City. The results of this study indicate that the development of professional competence of Indonesian language teachers at SMP N 21 Bengkulu City. The first role of MGMP as a change or update in improving teacher professionalism. Creating a conducive atmosphere in active learning. The second role of MGMP as a mediator to improve teacher competence in MGMP Indonesian language at the school level. MGMP's third role as a supporting agent MGMP as a supporting agent, because MGMP facilitates teachers to be able to make various innovations in classroom management and school management.